The importance of establishing the competent tax judiciary in Iraq between necessity and reality: Analytical study - Muhammod, Naheda Abdulghani Muhammod (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
The issue of organizing tax observation and how to collect it - including judicial observation, is a subject that has attracted the attention of states from ancient times to the present. The researcher is study in this research about the judicial observation essence ,its importance and its specifications and types , and studies the judicial observation on the fulfilment of the tax laws in Iraq , and extent to which the Iraqi tax institution needs a competent judicial tax. The research yielded important results, including the need to create a competent judicature tax in Iraq , as well as legislating special laws that regulate the work of this judiciary, such as the principles of tax trials , in order to enrich the tax judiciary, unify its path, and save it from confusion and volatility in it. as a result of the difference of opinions in the effectiveness of both the ordinary and the administrative judiciary to solve the disputes which happens about the tax law and its fulfilment.